Efecto de la temperatura sobre la velocidad de reacción del benzaldehído y n-propanol en la síntesis del di-n-propil acetal del benzaldehído - Delgado Gordillo, Exequiel Arnaldo (2018)
This research report aims to determine the effect oftemperature on the rate of chemical reaction of benzaldehyde and n-propanol in the synthesis of di-n -propil acetal of benzaldehyde. The research was carried outby the determination of the chemical kinetics of the rate ofreaction at temperatures other than 50° c and 70 ° c.according to this method, we submitted to the reactants inan acid medium with a light organic solvent. then installedthe distillation equipment to reflux with separator solvents light at temperature of 50 to 70 ° c; to obtain a volume ofconstant water chemical reaction product; thereby obtainingthe product. the following results were obtained:percentage of practical performance of acetal is 64% and 68% at 50° c and70° c respectively, boiling point was 198.5 ° c, 22° c density1,015; index of refraction 1.585; the activation energy of0.4158 kcal/mol, life time average at 50° c and 70° c is 2.4and 2.5 hours. The constants of reaction rates to 50° c and70° c in the synthesis of di-n-propilacetal of the benzaldehyde is 0. 000078 min-1 and 0. 000081min-according to the chemical and physical methods ofsynthesized acetal determined what di-n- propilacetaldelbenzaldehyde and the kinetic study demonstrates thatchemical reaction follows a first order behavior